Analyzing ISIS Strategy in Establishing an Islamic Caliphate Through Lykke’s Three-Legged Stool Strategy Model - Heavy Nala Estriani (Hasanuddin University, 2023)
This paper examines the strategy of the Islamic State of Iraq and Syria (ISIS) to establish an Islamic state called a caliphate in Iraq and Syria. In examining the case, this paper used the theory of strategy that comprised means, ways and ends introduced by Art. Lykke. Since its appearance in 2014, ISIS has occupied some prominent cities in Iraq and Syria to gain its objective of transforming the state into a caliphate. The group has used various ways or concepts to execute their objective through propaganda, beheading, modern technology network and the new media's role in recruiting new members. Regarding means or resources, the group has independently established and managed its economic income. However, the group has faced significant losses and decreases in the last two years. Thus, it has made achieving its objective of establishing a caliphate harder.